A Study of Catalogd: A Social Cataloging Application for Video Games - Mohd Iskandar, Shahathir (Journal of Computing Technologies and Creative Content, 2025)
This paper presents the development of Catalogd, a social cataloging application designed to enhance the experience of video game enthusiasts through efficient management of game libraries and facilitation of community interaction. The primary research objective is to create a platform that allows users to catalog their gaming experiences, discover new titles, and engage with other gamers. The scope of the study encompasses three user types—guest, registered, and admin users—each with varying levels of access and interaction within the app. Functionally, Catalogd includes modules for authentication, navigation, game discovery, catalog management, and social networking. The methodology employed is the Rational Unified Process (RUP), which guides the structured development of the application, ensuring that project goals are met within the set timeframe. Catalogd aims to address the gap in dedicated video game cataloging services and to provide insights into user engagement and gaming trends.